Emotional Intelligence And The Tendency To Behave Aggressively In Junior High School Students - Muna, I’smi Rodliyal; Hakim, Zun Azizul (Indonesian Scientific Publication, 2023)
This study aims to determine the relationship between emotional intelligence and the tendency to behave aggressively in senior high school students. The research method used in this study is the quantitative correlational method. The sample of this study consists of 190 8th grade junior high school students in Blitar, West Java. The data collection process is carried out by providing a Google Form containing an emotional intelligence scale and a tendency scale to behave aggressively. The analysis technique used to analyze the data is the product-moment Pearson correlation test. The result of this study shows a significant negative correlation between emotional intelligence and the tendency to behave aggressively among junior high school students (r = -0.373; p < 0.05). The hypothesis proposed is accepted, meaning that there is a significant negative relationship between emotional intelligence and the tendency to behave aggressively in junior high school students in Blitar, West Java. This means that the higher the emotional intelligence, the lower the tendency to behave aggressively in students.